BATTLE AT SEA : 3,000 YEARS OF NAVAL WARFARE - Grant, R. G. (DK Publishing, 2008)
A visual journey through 3,000 years of naval warfare — now in paperback! From the clash of galleys in Ancient Greece to deadly encounters between nuclear-powered submarines in the 20th century, explore every aspect of the story of naval warfare on, under, and above the sea